Design of Arduino-based LPG Gas Leak Detection Tool using MQ-6 Sensor - Pamungkas, Diaz Resnu; Setiawan, Agus; Widiyanto, Andi (Innovation, Technology, and Entrepreneurship Journal, 2024)
LPG (Liquefied Petroleum Gas) is a natural resource that has increased yearly consumption. LPG gas is used almost every time for human life in the household and industry sectors. LPG gas, besides being cheap, is also easier to use. However, the increasing use of LPG gas also increases the risk of fire or gas collection caused by LPG gas leaks. Therefore, a tool is needed to detect LPG gas leaks. So an LPG gas leak detector was made using the MQ-6 sensor, which can detect LPG gas leaks, and using a blower fan to overcome the collection of gas levels around LPG gas cylinders, using a buzzer as an alarm, using a servo to turn off the electricity so that an explosion does not occur, and use spray foam to spray onto the tube and stove if the blower cannot handle the LPG gas leak. Overall, the design components are controlled by Arduino Uno R3. This testing process takes an average of 9.56 seconds. If it is less than 9.56 seconds, then only one action is enough: the blower fan, active buzzer, and pump 1. If it is more than 9.56 seconds, the second action will be continued: spraying foam and turning off the electricity. On the other hand, there is an opportunity to bring this tool to commercial. Many households need this tool to save their house from fire threats. Finally, this tool can be a development tool for solving an incident from gas and will be a best-selling tool.